A rapid aerodynamic prediction method for unconventional transonic aircraft configurations - Prince, Simon A.; Di Pasquale, Davide; Garry, Kevin; Nuzzo, Cristina (International Council of the Aeronautical Sciences (ICAS), 2018)
This paper presents some results comparing the use of the Full Potential equations, coupled with the turbulent integral boundary layer equations for aircraft transonic cruise analysis. Use of such a method in the conceptual design stage is shown to be capable of yielding accurate enough data in a few minutes on a single processor, where Navier - Stokes simulations on 100+ processors take several days.
Keywords: Transonic Aerodynamics; Aircraft Design; CFD